Ecofriendly flame-retardant composite aerogel derived from polysaccharide: Preparation, flammability, thermal kinetics, and mechanism. (1st October 2021) - He, Hualing; Wang, Yushu; Yu, Zhicai; Liu, Jinru; Zhao, Yuhang; Ke, Yushi
Abstract: Bio-based aerogel (polysaccharide cryogel) have led to a growing interest because of eco-friendliness, sustainability and excellent thermal insulation properties. Herein, we report an eco-friendly strategy to construct lightweight and porous sodium alginate/ carboxymethyl cellulose/ chitosan polysaccharide-based composite aerogels (SCC-B) by freeze-drying and post-cross-linking technology. The ester cross-linking of polysaccharide component achieved strong web-like entangled structure when using 1, 2, 3, 4-butanetetracarboxylic acid and sodium hypophosphite as eco-friendly co-additives, meanwhile significantly improved flame retardancy of SCC-B due to phosphorylation. The thermal kinetic behavior of SCC-B was investigated by Flynn-Wall-Ozawa and Kissinger models. Results indicated that peak heat release rate and total heat release of SCC-B decreased from 30 W/g to 20 W/g and 15 kJ/g to 10 kJ/g, respectively. Furthermore, the second-degree burn time of SCC-B reached up to 87.1 s under heat exposure of 11.3 kW/m 2 . These characteristics combine to suggest hopeful prospects for use of SCC-B in the fields of fire-protection clothing as a renewable flame-retardant material. Graphical abstract: Unlabelled Image Highlights: An eco-friendly flame retardant composite aerogel was successfully prepared. The ester cross-linking of polysaccharide form a strong web-like structure. The resultant composite material can effectively suppress heat release. The thermal kinetic behavior of aerogel was investigated by Flynn-Wall-Ozawa and Kissinger models.